Financial literacy and the demand for financial advice - Calcagno, Riccardo; Monticone, Chiara (Journal of Banking & Finance, 2015)
The low level of financial literacy across households suggests that they are at risk of making suboptimal financial decisions. In this paper, we analyze the effect of investors’ financial literacy on their decision to demand professional, non-independent advice. We find that non-independent advisors are not sufficient to alleviate the problem of low financial literacy. The investors with a low level of financial literacy are less likely to consult an advisor, but they delegate their portfolio choice more often or do not invest in risky assets at all. We explain this evidence with a highly stylized model of strategic interaction between investors and better informed advisors with conflicts of interests. The advisors provide more information to knowledgeable investors, who anticipating this are more likely to consult them.